Analysis of cracks in the welded zone of stainless steel pipe used in high-pressure decomposer equipment. (August 2019) - Husaini,; Najib, M; Hasanuddin, I
Abstract: ASTM A276 was the material used in a stainless steel pipe inside High-Pressure Decomposer (HPD) equipment that was being used in the fertilizer industry. The pipe had 3 mm of thickness and was operated at a pressure and temperature of approximately 1.7 MPa and 130°C respectively. Leaking was observed from a crack in a welded area of the Heat Affected Zone (HAZ) and caused the factory to shut down. From the study results, the stress intensity factor ( KI ) value at the crack tip was calculated to be approximately 1244 Mpa.m 1/2, whereas the fracture toughness ( KIC ) of the pipe material value is 499.9 MPa.m 1/2 . It can be inferred that due to the KI value being higher than the KIC value, then crack propagation occurred in the welded zone until it penetrated through the pipe wall. The cracking was also influenced by the presence of residual stresses and corrosive fluid flowing in the pipe which produced Stress Corrosion Cracking (SCC). It was further found that the welding process used to join the pipe produced porosity defects, which in turn caused porosity coalescence under the pressure of the pipe in operation, allowing crack propagation to occur and penetration of the pipe wall.